Manajemen Perawatan Luka Akut - Endang Murwaningsih; Agung Waluyo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to prevent complications after laparotomy surgery and provide an overview of the education needed for patients and families. The method used is a case report of a patient after laparotomy on day 8 of treatment with colon cancer with a stoma attached. The results showed that the patient had a better quality of life with the comfort of the dressing provided and a decrease in the pain scale. In conclusion, the importance of involving the family in care, education, and interprofessional collaboration is the key to successful treatment to prevent the further impact of acute wounds becoming chronic wounds, resulting in longer patient days. Keywords: Education, Acute Wound Management, Wound Healing Process